Preparation and Performance Evaluation of Polymeric Microspheres Used for Profile Control of Low-Permeability Reservoirs - Fajun Zhao; Hongbao Zhang; Yanping Wu; Dawei Wang; Yufei Zhang (Journal of Chemistry)
To improve in-depth profile control in a low-permeability reservoir, polymeric microspheres were used. A distillation–precipitation polymerization method was adopted to prepare nanometer-sized polymeric microspheres, whose structure, apparent pattern, thermal endurance, particle size, hydration, and swelling capacity were tested and analyzed by a series of techniques, including infrared spectroscopy, scanning electron microscopy, thermogravimetry, high-pressure and high-temperature rheometry, and dynamic light scattering. The prepared polymeric microspheres were copolymerization products of acrylamide, acrylic acid, and methyl methacrylate that were uniformly round with a centralized size distribution. The nanometer-sized microspheres had satisfactory hydration/swelling performance, indicating that they could act as oil displacement profile control agents. With the increase of shear rate, the apparent viscosity of the polymeric microspheres was significantly reduced, and the fluid possessed a pseudoplastic behavior. When the shear rate was 100–1000 s−1, the fluid demonstrated a Newtonian fluid behavior. After the polymeric microspheres were hydrated, the particle size distribution curve shows a normal distribution, reaching a maximum swelling size of 21.3 times that of the original microspheres. The plugging performance and deformability of the polymeric microspheres gradually enhanced with swelling time, which makes the microspheres effective pore channel plugging agents for delivering a better in-depth profile control effect in rock cores with lower permeability. The core flooding test showed that, for the heterogeneous core with a permeability of 10 μm2, polymer microspheres have good plugging effect.